S3A:7 Neutrophil extracellular traps markers are elevated in patients with systemic lupus erythematosus. (21st March 2018) - Jeremic, I; Djuric, O; Bonaci-Nikolic, B
Abstract : Introduction: Impaired removal of apoptotic waste in patients with systemic lupus erythematosus-SLE has been long known as important factor that trigger autoimmune response. Neutrophil extracellular traps could be another source of autoantigens in patients with SLE. Methods: We analysed sera from 84 SEL patients (60 patients had one sample and 24 patients were followed 2 or 3 times) and 50 healthy blood donors. Serum levels of myeloperoxidase, B-cell activating factor-BAFF, cell free DNA, complement components C3 and C3, antibody to dsDNA by CLIFT end ELISA assays, netolitic activity and DNAse I were measured. Results: Patients with SLE had higher cfDNA (1.69±0.23 vs 1.42±031 ng/mL, p=0.0003), MPO (1607±2353 vs 1503±1106, p<0.05) and BAFF levels (160735±2353.23 vs 891.16±184.31, p<0.05). DNAse concentration was also lower in healthy controls (5.84±5.72 vs 9.38±6.97, p<0.05). BAFF showed strong correlation with anti-dsDNA antibodies determined by ELISA method (ρ=0.564, p=0.000), MPO activity (ρ=0.256, p=0.021), DNAse I concentration (ρ=0.27, p=0.012) and cfDNA concentration (ρ=0.262, p=0.014). DNA determined by ELISA test showed correlations with DNAse concentration (ρ=0.249, p=0.022), DNA determined by CLIFT (ρ=0.341, p=0.001) and C3 complement component (ρ=−0.4, p=0.023). MPO activity showed correlations with cfDNA levels (ρ=0.386, p=0.001), DNAse concentration (ρ=0.501, p=0.000), and anti-MPO antibodies (ρ=0.293, p=0.006). Cell free DNA levels additionally correlated with DNAse activity (ρ=0.288, p=0.007) as well with netolytic activity (ρ=0.244, p=0.026). Netolytic activity also correlated with anti-dsDNK antibodies determined by ELISA (ρ=−0.299, p=0.039). Conclusions: Increased NETs` footprints (myeloperoxidase and cfDNA) are present in lupus sera. As probably compensatory mechanism increased DNAse I concentrations also were found in lupus sera. NET burden is followed by production of various antibodies recognising different NET structures.